2009
DOI: 10.1111/j.1365-2036.2008.03894.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: open, small‐incision or laparoscopic cholecystectomy for symptomatic cholecystolithiasis

Abstract: SUMMARY BackgroundLaparoscopic cholecystectomy has become the method of choice for gallbladder removal, although evidence of superiority over open and small-incision cholecystectomy is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 84 publications
0
42
0
1
Order By: Relevance
“…A subgroup analysis of high-quality trials showed a shorter operative time for the small-incision OC than LC (weighted mean difference, random effects 16.4 min, 95% CI: 8.9-23.8 min) [15]. Compared with the small-incision OC, the self-reported quality of life up to 30 days after LC is higher; 2326 (95% CI: 2187-2391) and 2411 (95% CI: 2334-2502), respectively, P = 0.03 [16].…”
Section: Laparoscopic Cholecystectomymentioning
confidence: 99%
See 1 more Smart Citation
“…A subgroup analysis of high-quality trials showed a shorter operative time for the small-incision OC than LC (weighted mean difference, random effects 16.4 min, 95% CI: 8.9-23.8 min) [15]. Compared with the small-incision OC, the self-reported quality of life up to 30 days after LC is higher; 2326 (95% CI: 2187-2391) and 2411 (95% CI: 2334-2502), respectively, P = 0.03 [16].…”
Section: Laparoscopic Cholecystectomymentioning
confidence: 99%
“…A meta-analysis comparing LC with the small-incision OC (the length of incision of less than 8 cm) demonstrated that both techniques had similar rates of mortality; intraoperative, minor and severe post-operative complications (without bile duct injuries, BDI); BDI; total complications; and post-operative convalescence [15]. A subgroup analysis of high-quality trials showed a shorter operative time for the small-incision OC than LC (weighted mean difference, random effects 16.4 min, 95% CI: 8.9-23.8 min) [15].…”
Section: Laparoscopic Cholecystectomymentioning
confidence: 99%
“…Bile duct injury, mainly incisions or damage from disconnection after misidentification of the common bile duct as the gallbladder duct, was reported [48]. Common bleeding sites included the cystic artery, gallbladder bed (located near branches of the middle hepatic vein), and hepatic artery [46][47][48]. These complications were most often related to the technical competence of the surgeon, the extent of inflammation or adhesion, or surgery being contained for too long [36,[48][49][50][51].…”
Section: Commentarymentioning
confidence: 99%
“…Compared to an open approach, minimally invasive techniques have proven effective in reducing surgical trauma, thereby improving patient recovery and length of hospital stay [1,2]. Benefits of improved postoperative pain and cosmesis are now well established for many operations [3][4][5].…”
Section: Introductionmentioning
confidence: 99%